Neuropsychological phenotype and psychopathology in seven adult patients with Phelan‐McDermid syndrome: implications for treatment strategy. (17th February 2016) - Egger, J. I. M.; Zwanenburg, R. J.; van Ravenswaaij‐Arts, C. M. A.; Kleefstra, T.; Verhoeven, W. M. A.
Abstract : Phelan‐McDermid syndrome presents with specific deficits in neurocognition, cerebellar regulatory functioning and enhanced vulnerability for the development of atypical bipolar disorder. Abstract : Phelan‐McDermid syndrome (PMS) or 22q13.3 deletion syndrome is characterized by a variable degree of intellectual disability, impaired speech and language as well as social communicative skills and mild dysmorphic features. The SHANK3 gene is thought to be a major contributor to the phenotype. Apart from the syndrome‐associated autistic features, symptoms from the bipolar spectrum can be discerned, in particular behavior instability and fluctuating mood culminating in a (hypo)manic state. In case of coincident major somatic events, a deteriorating course may occur. This study comprises seven adult patients (four females and three males; aged 21–44 years) with genetically proven PMS. Data from medical records were collected and extensive assessment of neuropsychological variables was performed to identify cognitive characteristics and their relation with psychopathology and treatment. All patients showed profound communication deficits and their developmental functioning ranged from 1.0 to 6.3 years. In addition, they had slow speed of information processing, impairment of attentional and executive functions and cognitive alexithymia. As to psychopathology, features from the affective and anxiety domains were prominent findings in these seven patients suggesting the presence of a bipolar spectrum disorder that could be effectively moderated with mood‐stabilizing agents. Results are discussed in terms of the putative involvement of structural brain abnormalities, in particular cerebellar vermis hypoplasia and corpus callosum thinning and their cognitive and emotional sequelae. It is concluded that the treatment of 22q13.3‐associated psychopathology should include prescription of mood‐stabilizing agents in combination with individually tailored contextual neuropsychological measures.